Evaluating Tools for Live Imaging of Structural Plasticity at the Axon Initial Segment - Dumitrescu, Adna S.; Evans, Mark D.; Grubb, Matthew S. (Frontiers in Cellular Neuroscience, 2016)
The axon initial segment (AIS) is a specialized neuronal compartment involved in the maintenance of axo-dendritic polarity and in the generation of action potentials. It is also a site of significant structural plasticity—manipulations of neuronal activity in vitro and in vivo can produce changes in AIS position and/or size that are associated with alterations in intrinsic excitability. However, to date all activity-dependent AIS changes have been observed in experiments carried out on fixed samples, offering only a snapshot, population-wide view of this form of plasticity. To extend these findings by following morphological changes at the AIS of individual neurons requires reliable means of labeling the structure in live preparations. Here, we assessed five different immunofluorescence-based and genetically-encoded tools for live-labeling the AIS of dentate granule cells (DGCs) in dissociated hippocampal cultures. We found that an antibody targeting the extracellular domain of neurofascin provided accurate live label of AIS structure at baseline, but could not follow rapid activity-dependent changes in AIS length. Three different fusion constructs of GFP with full-length AIS proteins also proved unsuitable: while neurofascin-186-GFP and NaVβ4-GFP did not localize to the AIS in our experimental conditions, overexpressing 270kDa-AnkyrinG-GFP produced abnormally elongated AISs in mature neurons. In contrast, a genetically-encoded construct consisting of a voltage-gated sodium channel intracellular domain fused to yellow fluorescent protein (YFP-NaVII–III) fulfilled all of our criteria for successful live AIS label: this construct specifically localized to the AIS, accurately revealed plastic changes at the structure within hours, and, crucially, did not alter normal cell firing properties. We therefore recommend this probe for future studies of live AIS plasticity in vitro and in vivo.